Clinicomycological Profile of Dermatophytosis in Tripura – An Institution Based Cross Sectional Study - Syamal K. Chakrabarti; Shibabrata Bhattacharjee; Bidhan Goswami; Shauli Sengupta; Bhaskar Bhattacharjee (Indian Journal of Dermatology)
Background In a small state like Tripura, a surge in prevalence of superficial dermatophytosis has been observed from April to September among the population of both tribal and non-tribal groups having different lifestyle, different food habit, and different socioeconomic status. Studies from different region reveal varying pattern of etiological distribution of the disease. But till date no research study has been initiated in Tripura on clinicomycological profile of dermatophytosis. Objectives This study was undertaken with the objectives to estimate the proportion of different fungal species associated with dermatophytosis among the patients attending Dermatology Outpatient Department of a Tertiary care hospital of Tripura and also to determine possible association of different clinical parameters with fungal species if any. Materials and Methods A total of three hundred and ninety-one (391) new cases of dermatophytosis attending Dermatology Outpatient Department of a Tertiary care teaching hospital of Tripura were included in this study from June, 2021 to May, 2022. All the specimens were assessed by direct microscopic examination and in vitro culture. Fungi were identified on the basis of their macroscopic and microscopic features with the help of lactophenol cotton blue staining and urease test. Results There was a male preponderance among cases and maximum patients belonged to 21-40 years age group. Trichophyton schoenleinii was the most common fungal species (52.1%) grown in culture followed by Trichophyton rubrum (26.9%). Conclusion In contrast to previous study results from different parts of India, Trichophyton schoenleinii was the most common isolated fungal species from this part of northeast India, and Tinea corporis (41.3%) was the most prominent clinical manifestation of dermatophytosis.